2005
DOI: 10.2214/ajr.04.1644
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the Intrinsic Muscles of the Hand: Spectrum of Imaging Findings and Clinical Correlation

Abstract: MRI of the hands is useful and correlates well with clinical findings in patients with intrinsic hand muscle abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The accuracy of observers and the interobserver agreement in MRI depends on the type of lesion in the hand and wrist, and may vary even in experienced radiologists [4,5]. In a recent pilot study, it was demonstrated that SPECT/CT is more specific than MRI concerning the detection of clinically relevant lesions in patients with non-specific wrist pain [6].…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of observers and the interobserver agreement in MRI depends on the type of lesion in the hand and wrist, and may vary even in experienced radiologists [4,5]. In a recent pilot study, it was demonstrated that SPECT/CT is more specific than MRI concerning the detection of clinically relevant lesions in patients with non-specific wrist pain [6].…”
Section: Introductionmentioning
confidence: 99%
“…The ulnar nerve passes through the Guyon canal in the wrist, and many lesions may affect the ulnar nerve at this site, such as ganglion cysts, nerve sheath tumors, repetitive trauma, or hamate fractures (Fig 12) (71). MR imaging is useful in identifying the underlying cause of the compression, but the sensitivity and specificity have not been reported, to our knowledge (72).…”
Section: Nerve Lesions and Compression Neuropathiesmentioning
confidence: 82%
“…Several tumors may affect the intrinsic muscles of the hand. 11,14,43 A comprehensive review article was published in 2014 by Lee and Tandon. 44 They describe typical imaging features of focal lesions of the hand including several benign, malignant, and indeterminate lesions.…”
Section: Tumorsmentioning
confidence: 99%
“…A study by Andreisek et al in 19 patients with clinically evident or suspected intrinsic hand muscle abnormalities showed that MR imaging of the hand is useful and correlates well with clinical findings in patients with posttraumatic syndromes, peripheral neuropathies, myositis, and tumorous lesions, as well as congenital abnormalities. 14,15 Because there is sparse literature on the intrinsic muscles of the hand, this review article offers a comprehensive review of muscle function and anatomy, describes normal MR imaging anatomy, and shows a spectrum of abnormal imaging findings.…”
mentioning
confidence: 99%